2023
DOI: 10.1088/1555-6611/acc240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supercontinuum spectral widths in CCl4-core PCF with square and circular lattices in the claddings

Abstract: In this study, we demonstrate the ability to generate a broad supercontinuum (SC) spectrum with a low peak power of square (S-PCF) and circular (C-PCF) lattice photonic crystal fibers with hollow-core infiltrated with carbon tetrachloride (CCl4). The dispersion and nonlinear characteristics have been numerically analyzed in detail and compared to select the optimal structures for SC generation and evaluate the SC generation efficiency for each PCF. With four optimal proposed structures, the all-normal dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…Dispersion increases dramatically at short wavelengths (between 0.5 and 0.9 μm). This has been confirmed in several previous publications [26,29,43]. Also, as Λ increases, the dispersion becomes flatter and eventually monotonic.…”
Section: Optimization Of Pcf Characteristics For Scgsupporting
confidence: 87%
See 4 more Smart Citations
“…Dispersion increases dramatically at short wavelengths (between 0.5 and 0.9 μm). This has been confirmed in several previous publications [26,29,43]. Also, as Λ increases, the dispersion becomes flatter and eventually monotonic.…”
Section: Optimization Of Pcf Characteristics For Scgsupporting
confidence: 87%
“…For #F 2 , the SC spectrum can be extended from a part of the visible to MIR with even hundreds of times smaller power and short fiber length. Studies [14,29,31,48] also take advantage of the first air-hole ring diameter control model, but the SC spectral widths obtained are still limited with P values ranging from 0.45 to 10 kW. Moreover, with the same circular lattice, the work of Thuy et al [47] also showed a disadvantage in terms of spectrum broadening even using 7.4 and 24.7 times more peak power than ours.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations